Analisis Kemampuan Pemecahan Masalah Matematis Siswa Kelas VII Pada Materi Bentuk Aljabar Menggunakan Model Pembelajaran Problem Based Learning di SMP Kristen Palla - Dedo, Jefrian Rivaldi; Lubur, Dorothea N. L.; Making, Samuel Rex M.; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the mathematical problem-solving abilities of seventh-grade students at SMP Kristen Palla on the topic of algebraic expressions using the Problem Based Learning (PBL) model. This research employed a qualitative descriptive approach involving 20 student participants. Data were collected through problem-solving tests and interviews based on Polya's problem-solving steps: understanding the problem, devising a plan, carrying out the plan, and reviewing the result. Data analysis techniques using the Miles & Huberman model, namely; data reduction, data presentation, and drawing conclusions. The results showed that 10 students (50%) demonstrated high problem-solving abilities and achieved mastery, 6 students (30%) were in the medium category, and 4 students (20%) were in the low category. Based on the minimum mastery criterion (KKM) set at 75, 10 students (50%) met the standard, while the other 10 (50%) did not. The PBL model effectively supports students in developing critical thinking and problem-solving skills, making learning more meaningful and contextual. This study is expected to serve as a reference for teachers in implementing effective instructional strategies to enhance students' mathematical problem-solving abilities